Ureteroscopic Lithotripsy in Reverse Trendelenburg Position and Intraoperative Furosemide - zhang, cheng-jing; Xue, Song; Chen, Ren-Fu; Song, Zhen; Wang, Jun-Qi; WEN, Ru-Min; Cheng, Huan; Gao, Ke-Yu (Urology Journal, 2022)
Purpose: Upward stone migration is a significant problem during ureteroscopic lithotripsy (URSL) for upper ureteral stone, especially in absence of a ureteral occlusion device. In this study, we evaluated the novel strategy of reverse Trendelenburg position (RTP) and intraoperative diuresis for URSL without ureteral occlusion devices to avoid upward migration. Materials and Methods: From March 2018 to May 2020, a total of 119 URSLs were performed for upper ureteral stone (6-15 mm) with 67 procedures in RTP and 52 procedures in conventional lithotomy position (CLP). 20 mg of intravenous furosemide was administered prior to stone fragmentation with holmium laser only in RTP group. Patient demographics, stone side, stone size and operative characteristics were recorded and compared between the two groups. Results: Patient data, stone side and size were similar in the two groups. All procedures were complete without conversion to open surgery and major complications. There was no significant difference in the mean operative time (47.9 ± 7.7 min vs 45.3 ± 7.0 min, P = .062) and mean hospital stay (3.9 ± 0.9 d vs 4.0 ± 1.0 d, P = .336) between the RTP and CLP group. Stone upward migration was significantly less in RTP group (3.0%, 2/67) than in CLP group (19.2%, 10/52) (P = .005). Stone-free rate at one month after initial treatment was 92.5% in RTP group and 73.1% in CLP group (P = .004). Conclusion: The strategy of placing the patient in RTP and intraoperative administration of intravenous furosemide is simple, feasible and cost-effective in preventing stone upward migration during URSL with holmium laser in absence of a ureteral occlusion device for upper ureteral stone.